The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/ic101693v
|View full text |Cite
|
Sign up to set email alerts
|

Different ortho and para Electronic Effects on Hydrolysis and Cytotoxicity of Diamino Bis(Phenolato) “Salan” Ti(IV) Complexes

Abstract: Bis(isopropoxo) Ti(IV) complexes of diamino bis(phenolato) "salan" ligands were prepared, their hydrolysis in 1:9 water/THF solutions was investigated, and their cytotoxicity toward colon HT-29 and ovarian OVCAR-1 cells was measured. In particular, electronic effects at positions ortho and para to the binding phenolato unit were analyzed. We found that para substituents of different electronic features, including Me, Cl, OMe, and NO(2), have very little influence on hydrolysis rate, and all para-substituted or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
166
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(183 citation statements)
references
References 35 publications
16
166
1
Order By: Relevance
“…This rearrangement would change the overall charge of the compound from neutral to positive and may facilitate direct interaction with the DNA backbone through ionic interactions resulting in cell death (26). Another study shows that substitutions ortho to the binding phenolato unit of salan-type ligands influences the cytotoxicity of these types of Ti(IV) compounds because of electronic and steric effects (27). In addition, both the chirality of ligands (28) and ligand coordination to Ti(IV) (28,29) can affect the cytotoxicity of Ti(IV) compounds.…”
mentioning
confidence: 99%
“…This rearrangement would change the overall charge of the compound from neutral to positive and may facilitate direct interaction with the DNA backbone through ionic interactions resulting in cell death (26). Another study shows that substitutions ortho to the binding phenolato unit of salan-type ligands influences the cytotoxicity of these types of Ti(IV) compounds because of electronic and steric effects (27). In addition, both the chirality of ligands (28) and ligand coordination to Ti(IV) (28,29) can affect the cytotoxicity of Ti(IV) compounds.…”
mentioning
confidence: 99%
“…Nevertheless, numerous attempts to isolate pure LTiX 2 precursors failed; the water presumably originating from ligand preparation despite extensive purifications attempts (see SI), was sufficient to yield only hydrolysis products. The hydrolytic stability of the binuclear complexes was analyzed by 1 H NMR, adding 10% D 2 O to a DMSO-d 6 solution of the complexes, as previously described [15,16]. All salophan-Ti IV complexes were found to be highly stable, with t 1/2 above 100 h as expected for O-bridged clusters with no labile ligands [15,16,22,23,26].…”
mentioning
confidence: 99%
“…Complexes of Ti IV , budotitane ((bzac) 2 Ti(OEt 2 ), titanocene dichloride (Cp 2 TiCl 2 ) and their derivatives exhibited high anti-cancer properties against a range of cell lines with relatively minor side effects; nevertheless, rapid hydrolysis of the complexes in biologically relevant solutions to multiple unidentified species inhibited their utility [2][3][4][5][6][7][8][9][10][11][12][13]. Previously we have presented the diaminobis(phenolato) Ti IV complexes with particularly high cytotoxic activity, demonstrating higher hydrolytic stability than that of budotitane and titanocene dichloride [14][15][16][17][18][19][20][21][22][23][24][25]. Structure-activity relationship studies revealed that, for example, methyl groups on the nitrogen atoms (N-Me) greatly improve the hydrolytic stability of the complexes compared with no substitution (N-H) [22].…”
mentioning
confidence: 99%
See 2 more Smart Citations